2008
DOI: 10.1371/journal.pone.0004047
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Inversions between Human and Chimpanzee Lineages Caused by Retrotransposons

Abstract: The long interspersed element-1 (LINE-1 or L1) and Alu elements are the most abundant mobile elements comprising 21% and 11% of the human genome, respectively. Since the divergence of human and chimpanzee lineages, these elements have vigorously created chromosomal rearrangements causing genomic difference between humans and chimpanzees by either increasing or decreasing the size of genome. Here, we report an exotic mechanism, retrotransposon recombination-mediated inversion (RRMI), that usually does not alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 55 publications
(72 reference statements)
4
68
0
1
Order By: Relevance
“…Chaisson et al (2006) reported 426 inversions, and the refined method of Ma et al (2006) identified a similar number of inversions; however, only ∼59% of inversions were consistent in these studies (Chaisson et al, 2006). Lee et al (2008) reported 323 inversions among which 252 could be clearly characterized. These discrepancies indicate that identifying inversions is difficult, even for closely related species.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Chaisson et al (2006) reported 426 inversions, and the refined method of Ma et al (2006) identified a similar number of inversions; however, only ∼59% of inversions were consistent in these studies (Chaisson et al, 2006). Lee et al (2008) reported 323 inversions among which 252 could be clearly characterized. These discrepancies indicate that identifying inversions is difficult, even for closely related species.…”
Section: Introductionmentioning
confidence: 79%
“…Although human and chimpanzee are the most closely related species, the studies on micro-inversions between them (Chaisson et al, 2006;Feuk et al, 2005;Lee et al, 2008;Ma et al, 2006) showed large discrepancies. The earliest result reported 1576 putative inversions (Feuk et al, 2005), and later, it was found that the majority of these were artifacts (Chaisson et al, 2006;Kolb et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Although Robertsonian fusions and fissions appear frequently in studies of chromosomal rearrangement (as measured by changes in chromosome number), one of the most striking findings of comparative genomics is the high incidence of micro-inversions in the different genomes (Feuk et al, 2005;Lee et al, 2008;Zhao and Bourque, 2009). It may be that this largely undetected class of variation (inversions cannot be distinguished using whole chromosome painting, a data set that provides much of the basis for the recognition of ancestral constructs in Placentalia) functions as genomically localized barriers to recombination.…”
Section: Closing Comments and Future Prospectsmentioning
confidence: 99%
“…More structural changes (deletions) were found in the two Gm15 intervals, where there was higher transposon density, suggesting a correlation between structural changes and transposable elements. It is known that transposons can induce major genome rearrangements, including deletions, duplications, inversions, macrotransposition, and reciprocal translocations (Gray, 2000;Caceres et al, 2001;Lonnig and Saedler, 2002;Huang and Dooner, 2008;Lee et al, 2008;Zhang et al, 2009). We hypothesize that Gm15, with a higher transposon density, underwent more extensive structural changes (i.e., higher density of LTR retrotransposon, solo LTRs, and lower gene retention rate) and that transposable elements were likely an active force in this remodeling of a homoeologous chromosome in soybean (see Supplemental Figure 17 online).…”
Section: Ltr Retrotransposon Activity In Gm8 Gm15 and Pv5mentioning
confidence: 99%